Moving to Microsoft Windows Vista : visual quick project guide - Rizzo, John (Visual quickproject guide., 2007)
Packed with hundreds of new features, Windows Vista will open up new ways for users to take advantage of their PCs. Best-seller author John Rizzo will help users prepare for Vista with this useful guide. Recognizing that some new users of Windows Vista will only want to know what they need to accomplish their goal, this focused, four-color volume shows readers the quickest route to upgrading to the new OS. From determining if the reader's PC can run the new version of Windows to picking the right version of Vista to installing and setting the OS up, thisVisual QuickProject Guide uses a visual approach and concise explanations to make what can be a daunting task - updgrading to a brand new OS - easy and approachable. Each book in theVisual QuickProject Guide series now has a companion website featuring sample project files - making it even easier for users to work through each project as they read through the book. Other features on the companion website may include articles on getting the most out of the topic, a database of frequently asked questions, excerpts from the book, general tips, and more.